The balance between fumarate and malate plays an important role in plant development and postharvest quality in tomato fruit - Jiménez, Lidia; Pott, Delphine; Martinez-Ferri, Elsa; Fernie, Alisdair R; Vallarino Castro, José G.; Osorio-Algar, Sonia (My University, 2018)
Organic acids, produced as intermediates of the tricarboxylic cycle, play a crucial role in the plant primary metabolism and are considered as being ones of the most important quality traits in edible fruits. Even if they are key metabolites in a multitude of cellular functions, little is known about their physiological relevance and regulation. Transgenic tomato (Solanum lycopersicum) plants expressing constitutively a bacterial maleate isomerase, which converts reversibly maleate to fumarate, were generated in order to improve our knowledge about the role of organic acids in the crop and fruit metabolism. Growth and reproduction were affected by the unbalance of tricarboxylic cycle intermediates, as a dwarf phenotype and a flowering delay were observed in the transgenic plants. In addition, a delay in chlorophyll synthesis, a decrease in the numbers of stomata and significant changes in some photosynthetic parameters indicated alterations in central primary metabolism. Postharvest was also impaired, as transgenic fruits showed increased water lost and deterioration, indicating a possible role of the organic acids in cell wall metabolism. Finally, preliminary metabolomics analysis pointed out important changes during fruit ripening in flavor-related metabolites, such as acids and sugars, revealing the importance of organic acids in fruit metabolism. Taken together, these data indicate a pivotal role of tricarboxylic cycle intermediates, such as malate or fumarate, as regulatory metabolites. Besides their role in quality fruit characteristics, they are involved in a multitude of functions including growth and photosynthesis.
Keywords: Plantas - Metabolismo; Ácidos orgánicos; Postharvest; Tomato; Organic acids metabolism